Operational Research An International Journal - Zopounidis, Constantin; Matsatsinis, Nikolaos F.; Psarras, John.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Operational Research · An International Journal (ORIJ) publishes high quality scientific papers that contribute significantly to the fields of operational research and management science (OR/MS). ORIJ covers all aspects of OR including optimization methods, decision theory, stochastic models, simulation, game theory, queueing systems, inventory and reliability, among others. ORIJ focuses on papers presenting new theoretical insights and developments as well as real-world case studies illustrating the implementation of OR approaches in practice. Papers exploring the interactions of OR/MS with other relevant disciplines such as information technology, computer science, artificial intelligence, soft computing and electronic services are of particular interest. This is a unique feature of ORIJ compared to other existing OR journals, providing the means to explore new directions in OR/MS research in a interdisciplinary context. Overview papers from eminent scientists in significant fields of OR/MS that review the state-of-the-art in these fields, are also welcome. Officially cited as: Oper Res Int J.
Keywords: Operations research; Decision making; Management science; Computational intelligence; Operations Research/Decision Theory; Operations Research, Management Science; Computational Intelligence